2000
DOI: 10.1212/wnl.54.3.608
|View full text |Cite
|
Sign up to set email alerts
|

GCG genetic expansions in Italian patients with oculopharyngeal muscular dystrophy

Abstract: These data 1) further confirm PABP2 gene analysis as a valuable tool in OPMD diagnosis; 2) indicate that PABP2 gene mutations are always present among Italian patients with morphologically proven OPMD, suggesting genetic homogeneity of the disease; and 3) strengthen the putative role of mutated PABP2 protein in filamentous inclusions accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
5
36
0
Order By: Relevance
“…In patients from Germany, USA, Israel, UK, Italy and Japan the same mutation has been observed (Muller et al, 2001;Grewal et al, 1999;Blumen et al, 2000;Hill et al, 2001;Mirabella et al, 2000;Nagashima et al, 2000).…”
Section: Introductionmentioning
confidence: 54%
“…In patients from Germany, USA, Israel, UK, Italy and Japan the same mutation has been observed (Muller et al, 2001;Grewal et al, 1999;Blumen et al, 2000;Hill et al, 2001;Mirabella et al, 2000;Nagashima et al, 2000).…”
Section: Introductionmentioning
confidence: 54%
“…It is clear, however, that the severity of the phenotype varies even with carriers of the same size of (GCG) n PABPN1 mutation (Bouchard et al, 1997;Brais et al, 1998a, b). Preliminary studies have not demonstrated whether the size of the mutation influences the severity of the phenotype, at least when assessed by age of onset (Mirabella et al, 2000;Hill et al, 2001;Muller et al, 2001). Only carriers of the smallest (GCG) 8 PABPN1 mutation clearly appear to have a milder phenotype, with a later age of onset in the seventh decade characterized by ptosis and only mild dysphagia (Brais et al, 1998a, b;Hill et al, 2001;Muller et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism has a 1-2 % prevalence in North America, Europe, and Japan. Patients with a more severe compound heterozygote OPMD phenotype have also been observed in Italy and the UK (Mirabella et al, 2000;Hill et al, 2001). The cause of the increased severity in the other 80 % is unknown.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…These peripheral nerve lesions in OPMD have been reported previously in rare instances. [1][2][3][4][5][6][7][8] Clinical features consistent with denervation in OPMD include hyporeflexia or areflexia, 2,5-7 pes cavus, 2 fasciculations of limbs or tongue muscles, 2 amyotrophy distally in the limbs, 2,7 and distal hypesthesia in lower or upper limbs, often with impaired vibration perception. 2,[4][5][6] Whereas SNAPs and CMAPs were markedly reduced in our case, they are usually normal or slightly reduced in cases of OPMD with PNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary muscular origin of the disease is established, rare cases of peripheral nervous system (PNS) involvement have been described. [1][2][3][4][5][6][7][8] We report the case of a patient with OPMD and PNS involvement. …”
mentioning
confidence: 99%